Design and performance of the APPLE-Knot undulator - Ji, Fuhao (J Synchrotron Radiat, 2015)
Along with the development of accelerator technology, synchrotron emittance has continuously decreased. This results in increased brightness, but also causes a heavy heat load on beamline optics. Recently, optical surfaces with 0.1 nm micro-roughness and 0.05 µrad slope error (r.m.s.) have become commercially available and surface distortions due to heat load have become a key factor in determining beamline performance, and heat load has become a serious problem at modern synchrotron radiation facilities. Here, APPLE-Knot undulators which can generate photons with arbitrary polarization, with low on-axis heat load, are reported.